2013
DOI: 10.1159/000353458
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-to-Patient Ratios and Neonatal Outcomes: A Brief Systematic Review

Abstract: Background: Higher patient-to-nurse ratios and nursing workload are associated with increased mortality in the adult intensive care unit (ICU). Most neonatal ICUs (NICUs) in the United Kingdom do not meet national staffing recommendations. The impact of staffing on outcomes in the NICU is unknown. Objective: To determine how nurse-to-patient ratios or nursing workload affects outcomes in the NICU. Methods: Two authors (M.S., S.S.) searched PubMed, Medline, and EMBASE for eligible studies. Included studies repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 13 publications
1
46
0
3
Order By: Relevance
“…In addition, our study revealed that most nurses graduated from technical school rather than college. Several publications show that higher nurse-to-patient ratios and the higher proportion of nurses with a baccalaureate level education are associated with lower mortality rates [13], [14], [15]. Our findings highlight the urgent need to improve the quantity and education level of nurses in order to provide more accessible and satisfactory health services.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, our study revealed that most nurses graduated from technical school rather than college. Several publications show that higher nurse-to-patient ratios and the higher proportion of nurses with a baccalaureate level education are associated with lower mortality rates [13], [14], [15]. Our findings highlight the urgent need to improve the quantity and education level of nurses in order to provide more accessible and satisfactory health services.…”
Section: Discussionmentioning
confidence: 58%
“…Interviews with nurses, neonatologists and senior managers at the end of the study revealed that a government policy to redistribute staff to underserved areas had been implemented during the study. This led to loss of the following staff in study NICUs, where staffing levels were already below norms for intensive neonatal care [27]: 9 qualified nurses (almost 9% of total), 15 nurse assistants and 16 part-time and 5 full-time neonatologists (1 head of department). The majority had not been replaced.…”
Section: Discussionmentioning
confidence: 99%
“…Of the identified studies, two were from the UK;18 19 results from these two studies, however, are based on the same data from 1998 to 1999, prior to wide, systematic changes in the structure of neonatal care in the UK from 2003 onwards. The authors of the systematic review concluded that the included studies were too heterogeneous to support any particular nurse-to-patient ratio 4. Moreover, these studies have not been able to observe specific nurse-to-patient ratios at the individual patient level nor adequately account for unobserved confounding that may occur due to higher-risk patients being more likely to receive more intensive nursing support.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review4 of studies that examined nurse-to-patient ratios in neonatal clinical care settings identified six studies published between 1990 and 2010 14–19. As far as we are aware, only two further studies on this topic have been published since that time 12 20.…”
Section: Introductionmentioning
confidence: 99%